2012
DOI: 10.1103/physreve.86.026404
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of fast electron beam divergence in ultraintense laser-plasma interactions

Abstract: We report on the measurement and computer simulation of the divergence of fast electrons generated in an ultraintense laser-plasma interaction (LPI) and the subsequent propagation in a nonrefluxing target. We show that, at Iλ(2) of 10(20) Wcm(-2)μm(2), the time-integrated electron beam full divergence angle is (60±5)°. However, our time-resolved 2D particle-in-cell simulations show the initial beam divergence to be much smaller (≤30°). Our simulations show the divergence to monotonically increase with time, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…• [40,41]. For a target with tower structures on the front (shown at the top), there are considerably more higher energy electrons generated.…”
Section: General Characteristicsmentioning
confidence: 99%
“…• [40,41]. For a target with tower structures on the front (shown at the top), there are considerably more higher energy electrons generated.…”
Section: General Characteristicsmentioning
confidence: 99%
“…First is the well-known laser wake-field scheme 8 where a short pulse laser interacts with low density plasma to produce a directional and high energy electron beam; however, the typical currents produced by the wake-field mechanism are lower than is generally desired for the above applications. On the other hand, solid-target interactions produce high current electron beams but suffer from broad energy [9][10][11][12][13][14] and angular spread 15,16 . In this case, the relativistic or "hot" electron population is typically generated when an intense laser interacts with the pre-formed plasma generated by amplified spontaneous emission incident on the solid target starting a few ns before the short-pulse laser.…”
Section: Introductionmentioning
confidence: 99%
“…From radiation hydrodynamic calculation with MULTI2D, 10s of microns of under-dense plasma was created in front of the target before the main pulse arrived. Not only does this pre-plasma move the laser interaction interface from supra-critical solid density to the lower relativistic critical density, it also subjects the main pulse to instabilities [47,[58][59][60]132] Previous work by Yuan Ping et al [35] has shown that the early red shift in instantaneous wavelength on the rising edge of the specularly reflected pulse directly corresponds to the Doppler shift that arises from the motion of the critical surface. Their experimental traces, obtained from low-contrast pulse interactions, showed that the redshift was largest at the beginning of the pulse at nearly 6%, gradually dropped to 0% shortly after the reflection of peak of the pulse and ended with a 1.5% blueshift.…”
Section: Discussionmentioning
confidence: 99%
“…In WDM generation, it was found that a significant fraction of the hot-electrons generated by the laser was lost to heating the pre-plasma (due to a strongly magnetized under-dense plasma) and that switching to highcontrast pulses improved coupling to the bulk, resulting in increased target temperatures [13]. Recent experiments and laser-plasma simulations studying electrons generated with the cone-guided fast ignitor configuration have seen decreased angular spread [57,58] and increased coupling of laser energy into electrons of interest to FI [59,60] with increasing contrast. In TNSA, sharp target interfaces are important for creating large sheath fields [39] and thiner targets allow for more escaping electrons with higher mean and maximum energy [61], but significant pre-pulse can create microns of under-dense pre-plasma or even destroy too thin of a target.…”
Section: Issues Typical Of Ultra-intense Laser-plasma Interactionsmentioning
confidence: 99%
See 1 more Smart Citation